A new adaptive filtering algorithm for stereophonic acoustic echo cancellation. (March 2019) - Messini, Merouane; Djendi, Mohamed
Abstract: This paper addresses the stereophonic acoustic echo cancelation (SAEC) problem in teleconferencing system by adaptive filtering algorithm. We propose a new stereophonic version of the fast normalized least mean square (FNLMS) algorithm. The proposed algorithm is an extended version of the FNLMS algorithm to the stereophonic case with important improvement of the prediction part that becomes stable in the stereophonic case. The basic idea behind the proposed stereophonic fast normalized least mean square (SFNLMS) algorithm is the normalization of the predictor parameter by the inputs variance for each channel. Simulation results of a comparison between the proposed SFNLMS algorithm and the classical SNLMS version in term of convergence speed and stability are presented.